Benzoin condensation: a kinetic monitoring at the oil-water interface - Singh, Anshu; Kumar, Anil (ChemistrySelect, 2018)
The overall kinetics of condensation of benzaldehyde to benzoin has been discussed here with an aim to develop a better understanding of the change in reactivity of the interfacial reaction in the presence of co-solvents. A key aspect of the 'on water' reaction is the chemistry between solvent and reactants that occur at the oil-water interface. In particular the orientation of water molecules at the interface plays a key role in catalyzing the reaction. An initial increase in the rate constants of reaction is observed, followed by sharp fall in the reaction kinetics. An interesting interplay of hydrophobicity, hydrogen bonding and polarity of the binary mixture is inevitable in the present study. The observations are nevertheless important reference point for future investigations of 'on water' reactions.